A novel direct Z-scheme heterojunction of CoTiO3/ZnIn2S4 for enhanced photocatalytic H2 evolution activity. (12th March 2023) - Li, Rui; Shi, Qiongke; Zuo, Luyang; Chen, Yingjun; Li, Wenqiang; Fan, Huitao; Li, Bo; Wang, Liya
Abstract: The shortage of fossil energy has become a growing global concern. It is particularly important to make full use of the infinite solar energy resources, and transform them into sustainable and clean energy. The development of hydrogen energy has become a feasible solution to solve the energy shortage problem. The preparation of photocatalysts featuring efficient charge transfer channels and high hydrogen production activity provides a pathway for the development of hydrogen energy. In this paper, we report for the first time the direct assembly of 2D ZnIn2 S4 (ZIS) nanosheets on the surface of CoTiO3 (CTO). The synthesized CoTiO3 /ZnIn2 S4 (CTO/ZIS) photocatalyst features a direct Z-scheme charge transfer channel, which enhances the separation rate of photogenerated carriers, and accelerates the photocatalytic H2 evolution (PHE) rate. Without the assistance of any co-catalyst, the PHE rate of prepared CoTiO3 /ZnIn2 S4 was as high as 5.21 mmol g −1 h −1 . Moreover, the H2 evolution rate of CoTiO3 /ZnIn2 S4 almost did not decrease significantly after four consecutive 4 h cycles. This investigation provides a valuable approach for the exploitation of novel and efficient Z-scheme photocatalysts in the application of solar energy to hydrogen energy conversion. Graphical abstract: Using the Z-scheme CoTiO3 /ZnIn2 S4 photocatalyst, water is decomposed under visible light irradiation to produce large amounts of H2 . The conversion of solar energy to hydrogen energy is realized. Image 1 Highlights: This is the first report of in situ assembly of ZnIn2 S4 nanosheets on CoTiO3 surface. The as-prepared CoTiO3 /ZnIn2 S4 showed a new Z-scheme heterojunction. The CoTiO3 /ZnIn2 S4 heterojunction displayed an improved photocatalytic hydrogen evolution rate.